Safety of a feed additive consisting of folic acid for aquatic species (Chr. Olesen A/S and DSM Nutritional Products Ltd) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal, 2025)
Abstract Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety of a feed additive consisting of folic acid intended for use as a nutritional additive (functional group: vitamins, pro‐vitamins and chemically well‐defined substances having similar effects) for aquatic species. The characterisation, safety and efficacy of the additive have been assessed previously, however the FEEDAP Panel, considering the narrow margin between the requirement and the tolerated levels seen in some aquatic animal species, could not set a maximum safe level for all fish and crustacean species and considered that supplementation should not exceed the requirements of the different aquatic animal species. In addition, the FEEDAP Panel recommended that further research is conducted to allow setting a maximum safe level of folic acid in aquatic animal species. In the present assessment, the applicant submitted new information retrieved with an extensive literature search. After the assessment of the data newly submitted, the FEEDAP Panel reiterates its previous conclusions that the use of folic acid in aquatic animal species to cover their nutritional needs is considered safe. However, the Panel is not in a position to set maximum safe levels for all fish, crustacean and molluscs species. Considering the narrow margin between the requirement and the tolerated levels seen in some aquatic animal species, the FEEDAP Panel considers that supplementation should not exceed the requirements of the different aquatic animal species recognised by International scientific organisations.